The pass-through from inflation perceptions to inflation expectations - Stefanie J. Huber; Daria Minina; Tobias Schmidt (Deutsche Bundesbank, 2023)
This paper documents a strong relationship between households' perceptions about inflation over the past 12 months and households' short- and long-term expectations about future inflation. This relationship is strong during periods of high-inflation but even stronger during low-inflation periods. We establish a causal relationship by implementing a randomized information provision experiment in a large and representative survey to generate an exogenous variation in inflation perceptions. Our results show that household perceptions about past inflation drive their expectations about future inflation rates. The strength of the pass-through from perceptions to expectations varies across socioeconomic groups. We identify two critical moderating factors for this heterogeneity; differences in individual uncertainty about future inflation and information acquisition. Further, we show that the large majority of households rely on their shopping experience when forming their perceptions about past inflation and pay particular attention to food and fuel prices. The shopping experience affects inflation expectations indirectly - through perceptions.
Keywords: D10; D84; D90; E31; E52; G40; G50; 330; inflation dynamics; expectations; perceptions; uncertainty; household finance; monetary policy; randomized control trial